2015
DOI: 10.11648/j.ajtas.20150404.17
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Semi-Parametric Regression Analysis of Childhood Malnutrition in Gamo Gofa Zone: The Social and Economic Impact of Child Undernutrition

Abstract: Abstract:Major progress has been made over the last decades in reducing the prevalence of malnutrition amongst children less than 5 years of age in developing countries. Approximately 27% of children under the age of 5 in these countries are still malnourished. This work focuses on the childhood malnutrition in Gamo Gofa Zone, Ethiopia. This study examined the association between demographic and socioeconomic determinants and the malnutrition problem in children less than 5 years of age using Data obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The Bayesian semi-parametric model analysis revealed that sex, birth order, wealth quintile, mother's educational level and, sanitation facilities have a statistically signi cant effect (at 5% signi cance level) on the childhood stunting outcome. The study in agreement with previous studies (Khateb K., 2010;Fahrmeir & Khatab, 2008;Ferede Asena, 2015;N. B. Kandala et al, 2011;Mohammed & Asfaw, 2018;Takele, 2013;Yadav et al, 2015;Bacha, 2019) suggested that female children, children belonging to economically better households and born to educated mothers have higher HAZ score after controlling for other socio, economic and demographic covariates.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The Bayesian semi-parametric model analysis revealed that sex, birth order, wealth quintile, mother's educational level and, sanitation facilities have a statistically signi cant effect (at 5% signi cance level) on the childhood stunting outcome. The study in agreement with previous studies (Khateb K., 2010;Fahrmeir & Khatab, 2008;Ferede Asena, 2015;N. B. Kandala et al, 2011;Mohammed & Asfaw, 2018;Takele, 2013;Yadav et al, 2015;Bacha, 2019) suggested that female children, children belonging to economically better households and born to educated mothers have higher HAZ score after controlling for other socio, economic and demographic covariates.…”
Section: Discussionsupporting
confidence: 92%
“…Past studies have con rmed the association of growth faltering with a child's age but shows wide regional variations (15 months in Egypt, 17-30 months in Ethiopia) (Fahrmeir & Khatab, 2008;Ferede Asena, 2015;Mohammed & Asfaw, 2018;Takele, 2013). The mother's age at birth and her BMI also showed a signi cant non-linear relationship with childhood stunting outcome and is characterized by wide state-wise variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key determinants of child malnutrition is parental education, especially mother's education. Much of the literature has demonstrated that improved maternal education might be one of the defensive measures against children's poor nutritional status [10,11,[36][37][38]. This study also highlighted the fact that children of literate mothers (at least secondary education) were less likely to fall into anthropometric failure.…”
Section: Discussionmentioning
confidence: 68%